Preparation of organic–inorganic bio-based epoxy coatings with high anti-corrosive performance - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN (My University, 2023)
Epoxies derived from natural sources as an alternative to conventional petroleum-based epoxy resins have been used in sustainable coating applications. This study aims to create corrosion-resistant bio-based epoxy nanocoatings in the context of sustainable development. For this purpose, vegetable oil-based epoxy resins from cardanol and soybean oil were prepared. The structure of bio-based epoxies was confirmed by FTIR and 1H-NMR spectroscopy techniques. The epoxy functional silane precursor is synthesized from tetraethyl orthosilicate and (3-Glycidyloxypropyltrimethoxysilane by means of the sol–gel method. Amine curing agent and inorganic silica skeletons as polyhedral oligomeric silsesquioxanes and sol–gel precursor were added to the epoxy adduct and then cured. The curing kinetics of the formulations was followed by a differential scanning calorimeter. The chemical, mechanical, thermal, and anti-corrosive properties of the prepared coatings were investigated using various tests. The sustainable epoxy-based nanocoatings exhibited higher mechanical and thermal stability. In addition, the nanocoatings showed excellent corrosion resistance without the use of any anti-corrosive agent. The prepared green sustainable coatings will provide a more sustainable way to prepare bio-based coatings. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; POLİMER BİLİMİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; PHYSICS; POLYMER SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; PHYSICS, CONDENSED MATTER; Genel Kimya; Fizik Bilimleri; Yoğun Madde Fiziği; Polimerler ve Plastikler; Malzeme Kimyası; General Chemistry; Physical Sciences; Condensed Matter Physics; Polymers and Plastics; Materials Chemistry; Anti-corrosive coating; Organic–inorganic coating; Sustainable resources; Vegetable oil